Florida Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook: Food Safety Control Points - Todd A. Thrift; Matt J. Hersom; Max Irsik (EDIS)
AN171, is pages 11-36 of the full-color Florida Cow-Calf and Stocker Beef Safety and Quality Assurance Handbook, which is used for the voluntary Florida Beef Quality Producer program. This section covers points in beef production where there are legitimate food safety risks severe enough to warrant control. Produced as part of a cooperative program by Florida Cattlemen's Association, Florida Department of Agriculture and Consumer Services, and the University of Florida (IFAS) Extension Service. Published by the UF Department of Animal Sciences, October 2006.